Poetic cartographies: about routes, detours e existencial territories (Revista Apotheke, 2024)
Cartography has guided us in the production of this text, which aims to contribute to the debate concerning the approaches, methods and methodologies in the research and teaching of Visual Arts. In order to do it we present some excerpts from a project carried out in partnership with a public school located in the outskirts of the city. The goals were to offer opportunities school students to look into oneself and to one’s living spaces; look at everyday scenes and reflect on the possibilities of experience, on being-in-the-world, through Art. As we act on the borders between Art, Geography and Education, managing a number of actors - each one with their own research, teaching or extension aims – we worked to associate several sensitive and inventive methodological strategies, borrowed from or inspired by art itself. Our analysis are based on the studies related to space and place (Tuan, 2013; Bachelard, 1993); and concerning the methodological approaches of teaching and research grouped under the name of Art-Based Educational Research (Hernández, 2013; Charréu, 2019; Dias, 2013). The analysis of some of the cartographies together with their respective accounts highlights the potentialities of Art in these contexts of live research.
Keywords: cartography; arts-based educational research; living inquiry; space; place